The relationship between family communication patterns and identity crisis with emphasis on social Growth in high school female students in Yasuj city. - Mehrabi , Mahboobeh; Elahi, Mohammad (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: The present study aimed to investigate the relationship between family communication patterns and identity crisis with the mediating role of social growth among female high school students in Yasuj.Methods and Materials: The present study was conducted using a descriptive–correlational design. The statistical population included all female high school students in Yasuj, totaling approximately 3,500 individuals, from whom 300 students were selected through simple random sampling. Data collection was performed using the Family Communication Patterns Questionnaire developed by Koerner and Fitzpatrick, the Identity Crisis Questionnaire developed by Ahmadi, and the Ellis and Weitzman Social Growth Questionnaire. The questionnaires possessed acceptable validity and reliability according to previous studies. Data were analyzed using descriptive statistics, Pearson correlation coefficients, and structural equation modeling to examine the mediating role of social growth in the relationship between family communication patterns and identity crisis. Statistical analyses were conducted using SPSS and AMOS software at a significance level of p < 0.05.Findings: The findings revealed that family communication patterns had a significant negative relationship with social growth (r = -0.175, p = 0.002) and identity crisis (β = -0.24, p = 0.001). Conversation orientation was negatively associated with social growth (r = -0.349, p = 0.001), whereas conformity orientation showed a positive relationship with identity crisis (r = 0.251, p = 0.001). Furthermore, social growth had a significant positive effect on identity crisis (β = 0.42, p = 0.001). Structural equation modeling demonstrated that social growth significantly mediated the relationship between family communication patterns and identity crisis (β = -0.13, p = 0.001). The fit indices indicated satisfactory model fit (χ²/df = 2.11, RMSEA = 0.058, CFI = 0.95, GFI = 0.93), confirming the adequacy of the proposed model.Conclusion: The results indicated that family communication patterns play an important role in adolescents’ identity formation both directly and indirectly through social growth.